The prevalence of hearing loss in children in Colombia (2014)
Background. According to the Colombia National Statistics Administration (2005) in Colombia it is estimated that 17.3% of the registered population has permanent hearing limitations, of which 24 547 are under 10.Objective. This study aimed to determine the national prevalence of hearing loss in the population under 10 years of age between 2009 and 2011, identifying the variations in rates by type of hearing loss, unilateral or bilateral loss, age, and sex.Materials and methods. This descriptive, cross-sectional study, used data from the Individual Records of Health Procedures that was reported to the Colombian Ministry of Health during the period of observation and that was related to the diagnostic categories of hearing loss at discharge laid out in the ICD-10.Results. The analysis identified a hearing loss rate of 4.3 cases per 1,000 individuals under 10 years of age. The rate of sensorineural hearing loss cases was 5.1, 2.4 for conductive hearing loss and 1.2 for mixed hearing loss. Rates of 5.7 for bilateral hearing loss and 0.6 for unilateral losses were identified. A higher rate was found in children aged 5 to 10 years (2.4), than in children of 0-4 years of age (1.9).Conclusions. The evidence shows a high rate of hearing loss in children under 10 years of age. No significant differences between males and females are identified. Similar behavior was observed for both sexes in terms of sensorineural and conductive losses. However, there was a greater presence of mixed loss in females than in males.